Non-cardiac surgery in patients with continuous-flow left ventricular assist devices: a single institutional experience. (24th March 2017) - Chen, Carol W; Dumon, Kristoffel R; Shaked, Oren; Acker, Michael A; Atluri, Pavan; Dempsey, Daniel T
Abstract : With improvements in life expectancy for patients with continuous-flow left ventricular assist devices (LVADs), non-cardiac surgeons will increasingly encounter surgical problems in this population. 209 patients underwent LVAD placement between 10/1/2007 and 6/1/2015 at a single institution. Survival was compared between patients who had non-cardiac surgery (NCS) during the initial LVAD implantation hospitalization (n=36) and those who had NCS only in subsequent hospitalizations (n=33). Postoperative complication rates were examined. Index admission NCS was associated with lower 5-year survival compared with subsequent admission NCS (27.1% vs 39.4%, p=0.017). In subsequent admissions, the risks of bleeding and infectious complications were the same for elective or urgent NCS, but the risk of death was higher in the urgent surgery group. We conclude that elective NCS can be performed with low risk of death or LVAD dysfunction after sufficient recovery of patients from LVAD implantation.